The Effectiveness of Learning Using Virtual Laboratory Toward Student Critical Thinking Ability on Acid-Base Titration Lesson - Zera Seftiami Putri; Yenni Kurniawati (Journal of The Indonesian Society of Integrated Chemistry, 2021)
ABSTRACT The learning with experiment activities in the laboratory could increase students' critical thinking ability, but there were some obstacles in its implementation such as a lack of practical work tools in the laboratory.  To overcome it, it was used a learning media that could show practical work virtually.  This research aimed to know the difference in critical thinking ability between students taught by using a learning method with virtual laboratory and those who were taught by using conventional learning, and the effectiveness of learning using virtual laboratory toward student critical thinking.  The experimental method was used in this research with pretest-posttest non-equivalent control group design and purposive sampling technique.  The techniques of analyzing the data were t-test to know the difference in student critical thinking and N-gain test to know the effectiveness level.  The research findings showed that there was a difference in critical thinking ability between students of experimental and control groups, the posttest mean score of critical thinking ability of the experimental group was 81.91 and the control group was 75.22, this difference could also be seen from the calculation result of t-test that the significance score 0.002 was lower than 0.05, so H0 was rejected and Ha was accepted; effective learning.  It was proven by the obtained N-gain score of each student in the experimental group, 28 students were in the high N-gain category with 93.33% percentage and 2 students who were in the medium N-gain category with 6.67% percentage.